Attractive and repulsive residue fragments at the interface of SARS-CoV-2 and hACE2 - Jorge H. Rodriguez (Nature Portfolio, 2021)
Abstract The initial stages of SARS-CoV-2 coronavirus attachment to human cells are mediated by non-covalent interactions of viral spike (S) protein receptor binding domains (S-RBD) with human ACE2 receptors (hACE2). Structural characterization techniques, such as X-ray crystallography (XRC) and cryoelectron microscopy (cryo-EM), previously identified SARS-CoV-2 spike protein conformations and their surface residues in contact with hACE2. However, recent quantum-biochemical calculations on the structurally related S-RBD of SARS-CoV-1 identified some contact-residue fragments as intrinsically attractive and others as repulsive. This indicates that not all surface residues are equally important for hACE2 attachment. Here, using similar quantum-biochemical methods, we report some four-residue fragments (i.e quartets) of the SARS-CoV-2 S-RBD as intrinsically attractive towards hACE2 and, therefore, directly promoting host–virus non-covalent binding. Other fragments are found to be repulsive although involved in intermolecular recognition. By evaluation of their respective intermolecular interaction energies we found two hACE2 fragments that include contact residues (ASP30, LYS31, HIS34) and (ASP38, TYR41, GLN42), respectively, behaving as important SARS-CoV-2 attractors. LYS353 also promotes viral binding via several mechanisms including dispersion van der Waals forces. Similarly, among others, three SARS-CoV-2 S-RBD fragments that include residues (GLN498, THR500, ASN501), (GLU484, PHE486, ASN487) and (LYS417), respectively, were identified as hACE2 attractors. In addition, key hACE2 quartets identified as weakly-repulsive towards the S-RBD of SARS-CoV-1 were found strongly attractive towards SARS-CoV-2 explaining, in part, the stronger binding affinity of hACE2 towards the latter coronavirus. These findings may guide the development of synthetic antibodies or identify potential viral epitopes.